Duality theorems for nondifferentiable semi-infinite interval-valued optimization problems with vanishing constraints - Haijun Wang (SpringerOpen, 2021)
Abstract In this paper, we study the duality theorems of a nondifferentiable semi-infinite interval-valued optimization problem with vanishing constraints (IOPVC). By constructing the Wolfe and Mond–Weir type dual models, we give the weak duality, strong duality, converse duality, restricted converse duality, and strict converse duality theorems between IOPVC and its corresponding dual models under the assumptions of generalized convexity.